The Values of Islamic Education in the Amtsal (Parables) of the Qur’an: Nilai Pendidikan Islam dalam Al-Qur’an Kajian Amtsal (Perumpamaan) Al-Qur’an - Dwi Ratnasari; Eko Ngabdul Shodikin (At Turots: Jurnal Pendidikan Islam, 2021)
Al-Qur'an proverbs are one of the methods used by the Qur'an to visualize something abstract into something that looks real, this proverb is set out in various sentences, so understanding it requires careful and deep thought. The library research method or library research using several books of proverbs as the main source is the method the author uses in this study. The book of the Qur'an by orienting its education to humans in accordance with the elements of its creator, namely physical, spiritual, spirit and soul, which is closely related to the verses of the Qur'an itself. Therefore, there are many educational values ​​that can be learned from the verses of the Qur'an, especially through the study of the proverbs of the Qur'an. Among the educational values ​​that can be learned from the verses of the Qur'an are the Value of Faith and Tawhid, the Value of Obedience, the Value of Rational Thinking, the Value of Taqwa, and the Value of Creative. in education.